Efektifitas MA-11 dalam Meningkatkan Kecernaan Daun Kelapa Sawit Sebagai Pakan Ternak Alternatif - Sukaryani, Sri; Brahmana Dewa, Bayu; Ainul Yakin, Engkus (Jurnal Galung Tropika, 2024)
This study was conducted to determine the digestibility of Crude Protein (KcPK) and the digestibility of Crude Fiber (KcSK) of fermented oil palm leaves MA-11 with different incubation time treatments, namely 0 days, 3 days, 6 days, and 9 days. The observation data were processed using analysis of variance (ANOVA) from a Completely Randomized Design (CRD) and a follow-up test of Duncan's Multiple Range Test (DMRT). The study was arranged with four-way repetitions, namely T0: fermented oil palm leaves MA-11 for 0 days, T1: fermented oil palm leaves MA-11 for 3 days, T2: fermented oil palm leaves MA-11 for 6 days, and T3: fermented oil palm leaves MA-11 for 9 days. The results showed that the highest digestibility of crude protein in fermented oil palm leaves MA-11 was at T3, 58.11%, and the lowest at T0, namely 19.48%. The highest digestibility of crude fiber from MA-11 fermented oil palm leaves was found in T3 at 67.08% and the lowest at T0 at 57.54%. Fermented oil palm leaves using 6 ml of MA-11 and incubated for 0 days, 3 days, 6 days, and 9 days significantly increased crude protein and fiber levels on the longest day.